2022
DOI: 10.1371/journal.pone.0272874
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in SARS-CoV-2 seroprevalence in 3-to 16-year-old children: The Augsburg Plus study

Abstract: Background Currently, more than 30,200,000 COVID-19 cases have been diagnosed in Germany alone. However, data regarding prevalence of COVID-19 in children, both in Germany and internationally, are sparse. We sought to evaluate the number of infected children by measuring IgG antibodies. Methods Oropharyngeal swabs were collected between December 2020 and August 2021 to measure SARS-CoV-2, and capillary blood for the detection of SARS-CoV-2 antibodies (by rapid test NADAL® and filter paper test Euroimmun® ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
1
9
0
2
Order By: Relevance
“…58 Few data are available on seroreversion in children, although a few cohort studies have found that IgG antibodies waned (yet remained detectable), starting at two months up to 18 months post-infection, with higher antibody levels consistently observed among younger children. 7,913…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 Few data are available on seroreversion in children, although a few cohort studies have found that IgG antibodies waned (yet remained detectable), starting at two months up to 18 months post-infection, with higher antibody levels consistently observed among younger children. 7,913…”
Section: Introductionmentioning
confidence: 99%
“…Among seropositive individuals, estimates of antibody waning are variable with some suggesting that seroreversion occurs more rapidly among younger adults and those with mild or asymptomatic infections. [5][6][7][8] Few data are available on seroreversion in children, although a few cohort studies have found that IgG antibodies waned (yet remained detectable), starting at two months up to 18 months post-infection, with higher antibody levels consistently observed among younger children. 7,[9][10][11][12][13] In this prospective population-based cohort study, we used serological testing to assess the prevalence, seroconversion, and seroreversion of anti-SARS-CoV-2 antibodies in children and adolescents in Montreal, Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei der Beurteilung der Krankheitslast im Kontext eines pandemischen neuen Erregers, der bei Kindern häufig zu asymptomatischen Infektionen führt – wie bei der SARS-CoV‑2-Infektion – sind im Rahmen der Definition von Zähler und Nenner unterschiedliche Aspekte zu berücksichtigen: Der zeitliche Verlauf aller, einschließlich der asymptomatischen Infektionen (Nenner) ist beurteilbar durch: repetitive Untersuchung einer Kohorte oder durch Zeitreihen (wiederholte Querschnittuntersuchungen) mit Bestimmung von serologischen Markern (Enzyme-linked Immunosorbent Assay, ELISA; [ 14 ]). Zur Bestimmung der Seroprävalenz liegen aus Deutschland mehrere Querschnittuntersuchungen vor [ 1 , 8 , 10 , 14 , 18 ]. Die größte Studie mit über 10.000 Kindern und Jugendlichen wurde durch Bundesförderung möglich [ 14 ] und wurde deshalb hier als eine Quelle der Beurteilung der Häufigkeit von SARS-CoV‑2-Infektionen verwendet.…”
Section: Krankheitslast Durch Sars-cov‑2-infektionen Bei Kindern Im V...unclassified
“…Randomisierte Studien zur Effektivität der COVID-19-Kinderimpfstoffe erfolgten überwiegend in den ersten Jahren der Pandemie, weil nur dann ausreichend große Kohorten SARS-CoV‑2-naiver Kinder rekrutiert werden konnten. Sie berichten als Endpunkt „Erkrankung an COVID-19“, betrafen frühe VOC und zeigten eine akzeptable Effektivität zur Reduktion des Erkrankungsrisikos [ 5 , 10 , 15 ].…”
Section: Effektivität Und Etwaige Nebenwirkungen Der Impfungunclassified